Synthesis of hydrophilic carbon nanotubes via chemical vapor deposition using silicon oxide nanoparticles as seeds with potential biomedical applications - Hernández-Abril, Pedro Amado; Heredia-Cancino, Jose Antonio; Luque-Alcaraz, Ana Guadalupe; Higuera-Valenzuela, Hiram Jesús (Revista Mexicana de Física, 2025)
The research presented in this paper explores the synthesis of hydrophobic carbon nanotubes using silicon oxide nanoparticles as seeds through chemical vapor deposition. The study demonstrates the successful production of uniform-sized carbon nanotubes, essential for controlling their properties in diverse applications. By employing silicon oxide nanoparticles as catalysts, the pro- cess yields carbon nanotubes with specific characteristics suitable for potential biomedical applications. The investigation also highlights the dispersion in the size of silicon oxide nanoparticles and its potential influence on their collective behavior, empha- sizing the importance of this factor for future research endeavors. These findings contribute valuable insights to the field of carbon nanotubes, particularly in the context of biomedical applications, facilitating further advancements in this area.